DNA detection in tooth exposed to different temperatures: An in vitro study - Rama Raju Devaraju; Ramlal Gantala; Madhavi Ambati; Arjun Vemula; Jitender Reddy Kubbi; Srikanth Goud Gotoor (Wolters Kluwer Medknow Publications, 2014)
Introduction: Human identification is an important field of study and research in forensic science and aims at establishing human identity. Several biological materials such as bone, hair, a biopsy sample, saliva and blood have been employed in isolation of DNA for human identification. It is possible to obtain DNA from virtually all human body tissues with variations in the quantity and quality of the DNA extracted from each tissue. Aims and Objectives: A study was carried out in our department to detect the presence of DNA from burnt teeth samples at various temperatures and to highlight the importance of DNA obtained from tooth in identifying a deceased in fire accidents. Materials and Methods: The work included 13 extracted teeth of patients who were indicated for therapeutic extraction and those who were diagnosed clinically and radiographically with caries and periodontitis who were indicated for extraction. Out of the 13 extracted teeth, two were decayed (One had class I dental caries C 1 and the other was grossly decayed C 2 ), four were periodontally compromised teeth and the other seven were therapeutically extracted. The freshly extracted teeth were immediately subjected to varying temperatures, from 100°C to 800°C using a Delta burnout furnace for 15-20 minutes. They were cryogenically crushed using a mortar and pestle to make samples of the tooth, which were analysed for DNA. Results: When teeth were incinerated from 100°C-800°C, genomic DNA was obtained only between 100°C and 300°C whereas it was not obtained above this temperature. When the teeth were incinerated from 300°C to 800°C mtDNA was extracted from 300°C to 700°C, but no DNA was obtained above 700°C. Conclusion: Teeth are good sources for DNA, even in cases where the specimens are highly decomposed.